2022
DOI: 10.1155/2022/4159085
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Predictive Nursing Combined with Emotional Therapy on Rehabilitation Effect and Psychological State of Patients with Brain Injury after the Operation

Abstract: Objective. To explore the influence of predictive nursing combined with emotional therapy on the rehabilitation effect and psychological state of patients with brain injury after the operation and to analyze its application value to patients with brain injury after the operation. Methods. 70 postoperative patients with brain injury who went to our hospital for diagnosis and treatment were selected as the key figures of this experiment, including 31 female patients and 39 male patients. In order to ensure the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…In order to reduce the risk of adverse reactions during the period and improve the treatment effect of patients, it is still necessary to find efficient and safe nursing intervention in clinical practice. Predictive psychological nursing is one of the new clinical nursing models [8] , which advocates scientific and effective preventive measures to improve the emotional state of patients and improve the therapeutic effect of patients. Up to now, the predictive psychological nursing model has been applied in many clinical disease studies [9,10] , and all of them have achieved ideal results.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the risk of adverse reactions during the period and improve the treatment effect of patients, it is still necessary to find efficient and safe nursing intervention in clinical practice. Predictive psychological nursing is one of the new clinical nursing models [8] , which advocates scientific and effective preventive measures to improve the emotional state of patients and improve the therapeutic effect of patients. Up to now, the predictive psychological nursing model has been applied in many clinical disease studies [9,10] , and all of them have achieved ideal results.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%